2005
DOI: 10.1128/jcm.43.9.4877-4879.2005
|View full text |Cite
|
Sign up to set email alerts
|

Nosocomial Spread of a Staphylococcus hominis subsp. novobiosepticus Strain Causing Sepsis in a Neonatal Intensive Care Unit

Abstract: From 2002 to 2003, 32 isolates of Staphylococcus hominis subsp. novobiosepticus (SHN) were recovered from 21 patients, 18 of whom were neonates, with 13 considered to have late-onset SHN sepsis. All isolates from neonates had an indistinguishable pulsed-field gel electrophoresis pattern. Our data support SHN as an important nosocomial pathogen in neonates.Coagulase-negative staphylococci (CoNS) are now recognized as a major cause of nosocomial infections in neonatal intensive care units (NICUs) (8) and are res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
38
0
7

Year Published

2007
2007
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(49 citation statements)
references
References 22 publications
4
38
0
7
Order By: Relevance
“…BLAST analysis of these sequences revealed 100% similarity to S. hominis and S. epidermidis (Table 1) (GenBank accession numbers DQ831715-DQ831721). These results support the conclusion that the oxacillin-resistant bacterial community contaminating individual keyboards was not limited to MRSA and/or MRSE but was complex and included, for example, S. hominis (MRSH), a known nosocomial pathogen (Chaves et al, 2005).…”
supporting
confidence: 78%
“…BLAST analysis of these sequences revealed 100% similarity to S. hominis and S. epidermidis (Table 1) (GenBank accession numbers DQ831715-DQ831721). These results support the conclusion that the oxacillin-resistant bacterial community contaminating individual keyboards was not limited to MRSA and/or MRSE but was complex and included, for example, S. hominis (MRSH), a known nosocomial pathogen (Chaves et al, 2005).…”
supporting
confidence: 78%
“…All 21 isolates were resistant to nalidixic acid and susceptible to vancomycin. PCR analysis confirmed that all strains possessed a mecA gene homologue [9]. These findings are almost similar to the antibiotic sensitivity pattern in our study, as drugs found to be resistant to all patients were: Penicillin, erythromycin, ampicillin.…”
Section: Discussionsupporting
confidence: 77%
“…Sixty-eight isolates were from three hospitals in the USA (Illinois, n = 26; Mississippi, n = 1; New York, n = 41), 17 isolates were from one hospital in Spain, including 15 isolates from an outbreak among neonates and two isolates from adults that were not associated with the outbreak [17], five isolates were from a hospital outbreak among adults in Brazil [18], and 16 isolates were selected to be diverse by geography (Argentina, n = 1; Colombia, n = 1; Italy, n = 1; Japan, n = 1; Portugal, n = 2; Mexico, n = 3; Tunisia, n = 7) and by their different Xho I pulsed-field gel electrophoresis (PFGE) patterns that were characterized according to Bouchami et al [30]. In addition, American Type Culture Collection (ATCC) strains ATCC 27844 T and ATCC 700236 T were included as the S. hominis subsp.…”
Section: Methodsmentioning
confidence: 99%